Human cytomegalovirus infection and cognitive decline: insights from population and experimental studies - Yaiw, Koon Chu; Ferrer, Isidre A.; Söderberg-Nauclér, Cecilia; Religa, Dorota (Frontiers Media SA, 2026)
Human cytomegalovirus (HCMV), a ubiquitous DNA betaherpesvirus, is capable of persistent infection and immunomodulation, particularly in immunocompromised and elderly hosts. Emerging evidence links HCMV to neurodegenerative diseases through its multifaceted immunomodulatory effects. This review summarizes key viral architectures and mechanisms, epidemiological trends, and experimental data supporting HCMV's role in cognitive decline. We advocate for targeted antiviral strategies and vaccine development to clarify its contribution to neurodegeneration.